A Case of Systemic Lupus Erythematosus Mimicking Kikuchi-Fujimoto Disease - Çiçek, Demet; Dağlı, Adile Ferda (Fırat University, 2007)
Kikuchi-Fujimoto disease (KFD) or histiocytic necrotizing lymphadenitis is seen usually in patients with cervical lymphadenopathy and high fever. It may frequently occur in young women which has self limited process. KFD has a similar clinical and histopathological diagnosis and it is rarely accompanied with systemic lupus erythematosus (SLE). In this case report, a 36 years old woman who had axillary and cervical lymphadenopathy with fever, lose weight, arthralgia and skin rashes on her face has been admitted to hospital, is presented. Preliminary clinical diagnosis was KFD. Biopsy of enlarged lymph node showed SLE. We present this case because of the difficulties in differential diagnosing with SLE versus KFD. ©2007, Firat University, Medical Faculty

Kikuchi- Fujimoto Hastalığı (KFH) ya da histiositik nekrotizan lenfadenit klinik olarak en sık servikal lenfadenit ve yüksek ateş ile seyreden, sıklıkla genç kadınlarda görülen ve kendi kendini sınırlayabilen bir hastalıktır. Klinik ve histolojik açıdan sistemik lupus eritematozus (SLE) ile benzer özellikler gösteren KFH aynı zamanda nadiren SLE ile birlikte seyredebilmektedir. Bu çalışmada koltuk altı ve boyunda şişlik, ateş, kilo kaybı, eklem ağrıları ve yüzünde yara şikayeti ile hastaneye başvuran 36 yaşında bayan hasta KFH öntanısı ile yatırılıp lenf nodu biyopsinin histopatolojik incelemesinde SLE olduğu saptanandı. Olguyu her iki hastalığın ayırıcı tanısının zorluğuna dikkat çekmek amacıyla yayınlamayı uygun bulduk. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Kikuchi – Fujimoto Hastalığı ile Karışan Bir Sistemik Lupus Eritematozus Olgusu